Health literacy of adult women as a component of cervical cancer prevention in women - Ilievová, Ľubica; Sívková, Aneta; Meluš, Vladimír; Matišáková, Iveta (Kontakt, 2024)
Background: Cervical cancer is a preventable disease. The health literacy of women is a significant predictor of behaviour regarding their own health, along with the ability to search for, understand, and use health information, and plays an important role in the use of preventive and screening programmes. Objectives: To evaluate the health literacy level of women of reproductive age in relation to their knowledge of the issue of cervical cancer. Sample: The research sample consisted of women between the ages of 18 and 60 years old (n = 270). Methods: We collected data with the use of a self-constructed questionnaire focused on knowledge about cervical cancer and a standardised health literacy questionnaire (Health Literacy Questionnaire, hereafter the HLQ). Results: In the first five dimensions of the HLQ, the highest achieved score was recorded in the domain "Social support in the field of health" ( = 3.10 ± 0.35). The lowest scores were seen in the domains "Active care of one's own health" ( = 2.91 ± 0.33) and "Assessment of health information" ( = 2.91 ± 0.37). For the last four domains, the lowest score occurred in "Navigation of the health care system" ( = 3.42 ± 0.57), and the highest score was achieved in the domain "Understanding health information to the extent that the individual knows what to do" ( = 3.72 ± 0.45). Respondents assigned to the "sufficiently informed" group achieved a higher average score on the HLQ ( = 29.68 ± 3.13) than respondents assigned to the "insufficiently informed" group ( = 29.28 ± 3.29). Conclusion: It is necessary to increase the effectiveness and adequacy of patient education regarding the importance of passing preventive gynaecological examinations at annual intervals for the prevention of cervical cancer, as well as the possibility of vaccination against HPV.
Keywords: Early Detection of Cancer; vzdělávání pacientů jako téma; Middle Aged; průzkumy a dotazníky; Adult; nádory děložního čípku; Health Literacy; časná detekce nádoru; Slovakia; Human Papillomavirus Viruses; Slovenská republika; ženské pohlaví; Humans; Surveys and Questionnaires; Patient Education as Topic; lidé středního věku; Primary Prevention; lidské papilomaviry; zdravotní gramotnost; Uterine Cervical Neoplasms; dospělí; Female; primární prevence; lidé